Therapeutic effect of acupuncture combined montelukast sodium on cough variant asthma in children: A protocol for systematic review and meta-analysis. Issue 51 (23rd December 2021) - Zhou, Xiuling; Zhang, Ye; Liu, Le; Feng, Xiaochun; Zhang, Hongshi
Abstract: Background: Cough variant asthma in children is a special type of asthma. Although there are many effective cases of combined acupuncture and western medicine in the clinical treatment of this kind of children, there is no standardized acupuncture combined with western medicine to evaluate the curative effect. Therefore, combined with existing reports, a systematic review and meta-analysis of acupuncture combined with montelukast sodium in the treatment of cough variant asthma in children were carried out to obtain conclusive results. Methods: The following electronic databases will be searched: PubMed, the Cochrane Library, Embase, Web of Science, Medline, CNKI, Chinese Biomedical Literature Database, VIP, and Wan Fang databases. We will consider articles published between database initiation and October 2021. We will use Review Manager 5.4, provided by the Cochrane Collaborative Network for statistical analysis. Clinical randomized controlled trials related to acupuncture combined with montelukast sodium on cough variant asthma in children were included in this study. Language is limited to both Chinese and English. Research selection, data extraction, and research quality assessments were independently completed by two researchers. We then assessed the quality and risk of the included studies and observed the outcome measures. Results: This study provides a high-quality synthesis to assess the effectiveness and safety of acupuncture combined with montelukast sodium on cough variant asthma in children. Conclusion: This systematic review will provide evidence to determine whether acupuncture combined with montelukast sodium is an effective and safe intervention for patients with cough variant asthma in children. INPLASY Registration number: INPLASY2021110006.